Peningkatan Kapasitas Petani Cabai melalui Bimbingan Teknis Pengendalian Terpadu Penyakit Virus di Desa Wolasi, Kecamatan Wolasi, Kabupaten Konawe Selatan - Gusnawaty HS; Muhammad Taufik; Muhammad Botek (Jurnal Pengabdian, 2026)
Wolasi Village, located in Wolasi District, South Konawe Regency, is one of the major chili-producing areas in South Konawe. However, chili cultivation in the area is constrained by viral diseases that significantly reduce plant growth, yield, and fruit quality. Infected plants commonly exhibit stunting, leaf curling, mosaic symptoms, and malformed fruits, resulting in substantial economic losses for farmers. Disease management practices have largely relied on chemical pesticides, which are costly, often ineffective against viral diseases, and may pose environmental and food safety risks. Therefore, efforts are needed to improve farmers’ knowledge and skills in implementing more effective, affordable, and environmentally friendly disease management strategies. This community service program aimed to enhance the capacity of chili farmers in managing viral diseases through integrated disease management approaches. The activities were conducted using extension services, technical guidance, group discussions, and field demonstrations involving chili farmer groups in Wolasi Village. The training covered disease identification, the use of refugia plants, application of Trichoderma sp. biofungicide, utilization of citronella-based biopesticides, insect trapping techniques, and the judicious use of synthetic insecticides. The results showed an increase in farmers’ understanding of viral disease symptoms, transmission mechanisms, and integrated control techniques. Farmers actively participated in discussions and demonstrated improved skills in applying the introduced technologies. The program also increased farmers’ awareness of environmentally sustainable farming practices. In conclusion, the extension and technical guidance activities successfully strengthened farmers’ knowledge and skills in integrated viral disease management, thereby supporting sustainable chili production and reducing the risk of crop losses in Wolasi Village.